Distribuição geográfica histórica e recente da ariranha Pteronura brasiliensis (Carnivora, Mustelidae) - Colodetti, Amanda Francischetto (2014)
The giant otter is a semi-aquatic carnivore with diurnal and social habits. It is considered the largest otter in the world and also one of the most endangered. Was distributed widely in South America, occurring in all countries, except Chile. Their geographic range, however, has been changing in recent centuries. This study aimed (i) to estimate the historical and recent geographic range of the giant otter; (ii) to estimate the range contraction; and (iii) to relate the current occurrence of the species in Brazil to remaining vegetation and human population density (DPH). For this, we made an extensive survey of species occurrence records. The estimate of the geographic range was performed with the aid of alpha-shape algorithm and the area obtained for the historical and recent range was 9,817,116 km2 and 5,984,901 km2, respectively. The range contraction was estimated from the comparison between the historical and recent range, arriving to a result approximately 40% reduction of area, represented by the extinction of the giant otter in southern and eastern boundaries of the historic range. This contraction was analyzed in environments of aquatic and terrestrial ecoregions in order to verify the environments occupied by the species and also those of which it was extinguished. This analysis indicated that the species has disappeared not only from some environments, but at least a part of all occupied environments. Relate to the current occupation of the giant otter in Brazil with the remaining vegetation and the DPH, it was established that the range contraction is related primarily to anthropogenic influence. That's because the giant otter remained in areas with presence of remaining vegetation and low levels of DPH, while in areas where it is currently considered extinct environment was modified and the average DPH are high. There are several threats to the species mentioned in the literature, all of which related to anthropogenic activities, such as water pollution and habitat loss. A 40% reduction in its geographic range also represents the elimination of their ecological role in these regions, negatively impacting ecosystems and contributing to the biodiversity depletion. The results of this study may contribute to the development of conservation strategies, such as the giant otter reintroduction in areas where it was extinguished.